Moving down: women's part time work and occupational change in Britain 1991 - 2001 - Sara Connolly; Mary Gregory (Institute for the Study of Labor (IZA), 2007)
The UK's Equal Opportunities Commission has recently drawn attention to the 'hidden brain drain' when women working part-time are employed in occupations below those for which they are qualified. These inferences were based on self-reporting. We give an objective and quantitative analysis of the nature of occupational change as women make the transition between full-time and part-time work. We construct an occupational classification which supports a ranking of occupations based on the average level of qualification of those employed there on a full-time basis. Using the NESPD and the BHPS for the period 1991-2001 we show that perhaps one-quarter of women moving from full- to part-time work move to an occupation at a lower level of qualification. Over 20 percent of professional women downgrade, half of them moving to low-skill jobs; two-thirds of nurses leaving nursing become care assistants; women from managerial positions are particularly badly affected. Women remaining with their current employer are much less vulnerable to downgrading, and the availability of part-time opportunities within the occupation is far more important than the presence of a pre-school child in determining whether a woman moves to a lower-level occupation. These findings indicate a loss of economic efficiency through the underutilisation of the skills of many of the women who work part-time.
Keywords: 330; Female employment; part-time work; occupation; life-cycle; downgrade; over-qualification; Frauenerwerbstätigkeit; Teilzeitarbeit; Qualifikation; Arbeitsmarktsegmentierung; Panel; Zeitreihenanalyse; Schätzung; Großbritannien